Nematoda Gastrointestinal Pada Sapi Berdasarkan Ekologis Lingkungan - Zulfikar; M. Danil; Afkar; Wahyudi (Jurnal Serambi Engineering, 2024)
Gastrointestinal nematodes are a type of parasitic worm that is found in the digestive tract of humans and animals and can live in all areas, including fresh water, sea and land with a supportive environment. This research was to look at the percentage of gastrointestinal nematode infestation in cattle in Bireuen Regency as a lowland area from various levels of age groups and gender. The research samples were feces from 120 cattle divided into 3 age groups (0-6 months, 7-12 months, >12 months) and 2 genders(female and male). The examination was carried out using the centrifuge method. Samples are declared positive if gastrointestinal nematode eggs are found and the percentage is calculated using the prevalence formula and looking at differences in infestation levels analyzed using the chi-square formula. The research results showed that in the age group 0-7 months it was 35%, 7-12 months it was 22.5% and >12 months it was 15%. Between age groups the presence of these worms showed significant differences (P<0.05). Meanwhile, based on gender, female cows have a higher infestation, namely 23.9% compared to 15.2% for male cattle and there is a significant difference (P<0.05).